Influence of weather parameters on northern leaf blight development of maize incited by Exserohilum turcicum (Pass.) Leonard and Suggs in Nepal - Shishir Sharma (Cogent Food & Agriculture, 2023)
AbstractNorthern leaf blight (NLB) (Exserohilum turcicum) is the most important among disease of maize in cold and humid areas in Nepal. Environmental factors, particularly temperature and relative humidity, have a significant impact on the development of diseases. With the objective to correlate weather parameters with disease development, the experiment was conducted using three distinct varieties: Popcorn Gorkha 3 (Susceptible check), Rampur Composite (Standard and Local Check), and Rampur Hybrid 10 (Resistant Check). Numerous disease-related variables, including disease incidence percent, percent disease index (PDI), area under the disease progress curve (AUDPC), and the number of infected leaves per sample plant (IL/S), were correlated with mean relative humidity (RH), maximum temperature, and lowest temperature. The disease severity raised from 22.22% to 88.89% in Pop Corn Gorkha 3, from 11.54% to 30.77% in Rampur Composite, and from 3.33% to 10% in Rampur Hybrid 10, when the minimum temperature dropped from 11.2°C to 6.2°C. Correlation coefficient and principal component analysis showed that minimum and maximum temperature were negatively correlated while RH was positively correlated. According to the coefficient of determination (R2), certain meteorological factors contributed 94%–99% to the severity of the condition. The crucial step in developing disease management methods is a systematic examination of the correlation between meteorological variables and disease severity.